Dictionary of shipping terms - Brodie, Peter R. 1947- (Informa Law from Routledge, 2013)
Suitable for all professionals involved in maritime transport, including ship-owners, shipbrokers, freight forwarders, port authorities, average adjusters, and ship operators, this title contains concise definitions of maritime terms and phrases, including those used in liner, tramp and bulk shipping